p63 and p53: Collaborative Partners or Dueling Rivals? - Woodstock, Dana L.; Sammons, Morgan A.; Fischer, Martin (Frontiers in Cell and Developmental Biology, 2021)
The tumor suppressor p53 and its oncogenic sibling p63 (Np63) direct opposing fates in tumor development. These paralog proteins are transcription factors that elicit their tumor suppressive and oncogenic capacity through the regulation of both shared and unique target genes. Both proteins predominantly function as activators of transcription, leading to a paradigm shift away from Np63 as a dominant negative to p53 activity. The discovery of p53 and p63 as pioneer transcription factors regulating chromatin structure revealed new insights into how these paralogs can both positively and negatively influence each other to direct cell fate. The previous view of a strict rivalry between the siblings needs to be revisited, as p53 and p63 can also work together towards a common goal.